ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PENJUALAN MINYAK LOVINA PADA DISTRIBUTOR CV BUANA MANDIRI SEJAHTERA TIMIKA - Mikael Bato; Rosdiana (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This study aims to analyze the factors that influence the level of Lovina Oil sales at CV Buana Mandiri Sejahtera in Timika City. The factors analyzed include market conditions, seller ability, capital, and price. The sales data used in this study covers the period 2020 to 2023, with the data analysis techniques used being Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and multiple linear regression. The results of the analysis show that market conditions and prices have a positive and significant effect on Lovina Oil sales. On the other hand, seller ability and capital do not show a significant effect. The Kaiser-Meyer-Olkin (KMO) value of 0.863 indicates that the data has good sample adequacy. In addition, Confirmatory Factor Analysis (CFA) shows that one main component explains 89.875% of the variance in the data. The reliability test with Cronbach's Alpha produced a value of 0.969, indicating that the research instrument is very reliable. Based on the results of multiple regression, the R value of 0.943 indicates a strong relationship between the independent variables and the dependent variable. The conclusion of this study is that market conditions and price factors are the main determinants of Lovina Oil sales, while capital and seller ability require further evaluation